A case report of multi-compartmental lipoma of the hand. Issue 1 (1st January 2018) - Bocchiotti, Maria A.; Lovati, Arianna B.; Pegoli, Loris; Pivato, Giorgio; Pozzi, Alessandro
Abstract: This report shows a multi-compartmental lipoma that occupied a vast area of the hand volar compartment, the distal aspect of the Parona's space and infiltrated the dorsal compartment between the IV and V metacarpal bones. The mass was entirely removed through a dorsal approach, minimizing risks of neurovascular and tendinous lesions.